1997
DOI: 10.1103/physrevb.55.2840
|View full text |Cite
|
Sign up to set email alerts
|

Metastability and dynamics of the shock-induced phase transition in iron

Abstract: The shock-induced ␣͑bcc͒→͑hcp͒ transition in iron begins at 13 GPa on the Hugoniot. In the two-phase region above 13 GPa, the Hugoniot lies well above the equilibrium surface defined by G ␣ ϭG , with G the Gibbs free energy. Also, the phase transition relaxation time is uncertain, with estimates ranging from Ͻ50 ns to Ϸ180 ns. Here we present an extensive study of these important aspects, metastability and dynamics, of the ␣transition in iron. Our primary theoretical tools are ͑a͒ accurate theoretically based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
125
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(137 citation statements)
references
References 26 publications
10
125
0
2
Order By: Relevance
“…[4][5][6][7][8] The DFT-LDA calculations for graphite have repeatedly given excellent results for the in-plane and even the c-axis lattice constants of graphite. [9][10][11][12][13][14][15][16] Some of these authors have also claimed that their predictions for the interlayer binding energy are reasonably well compared to experiments. [11][12][13]16 However, there has been confusion in quoting the experimental data given by Girifalco and Lad 17 and some corrections such as that due to thermal effect have been ignored in comparisons between theoretical predictions and experiments.…”
Section: Introductionmentioning
confidence: 93%
“…[4][5][6][7][8] The DFT-LDA calculations for graphite have repeatedly given excellent results for the in-plane and even the c-axis lattice constants of graphite. [9][10][11][12][13][14][15][16] Some of these authors have also claimed that their predictions for the interlayer binding energy are reasonably well compared to experiments. [11][12][13]16 However, there has been confusion in quoting the experimental data given by Girifalco and Lad 17 and some corrections such as that due to thermal effect have been ignored in comparisons between theoretical predictions and experiments.…”
Section: Introductionmentioning
confidence: 93%
“…Iron was modeled using the two-phase equation of state of Ref. [28] (which reproduces accurately the α/ǫ phase boundary) , while Al and Al 2 O 3 were described by well calibrated equations of state in tabular form [29]. Neither Al nor Al 2 O 3 have any phase transformations in the P-T regime probed in these experiments.…”
mentioning
confidence: 99%
“…Common approaches rely on simple representations of the phase transformation rates, e.g. depending linearly on the difference between the chemical potentials of the two phases [28], which reproduce some of the dynamic behavior observed in shock experiments but cannot explain more complex experimental features such as the negative acceleration loops recorded in these or the water experiments [18,19]. We adopt here the phenomenological but physical picture proposed by Kolmogorov and others [3], where well defined domains of the growing phase increase their size at the expense of the parent phase through the motion of an infinitely thin interface.…”
mentioning
confidence: 99%
“…The uranium beam intensities needed to generate pressures approaching 1 Mbar will become available with the completion of the high-current upgrade of SIS-18 in the year 2009. In RWL experiments with intense ion beams, the typical compression times from zero to the maximum pressure are about 20 ns for the aluminum and about 10 ns for the iron samples considered here, which is comparable with the dissipative relaxation times of aluminum and iron (Swegle & Grady, 1985;Boettger & Wallace, 1997). Resent laser-driven experiments (Smith et al, 2007) have demonstrated that at such short time scales there exists a stiffer response than had been expected from previous slower ramp compression experiments and from models relying on either static or shock-wave experiments.…”
mentioning
confidence: 68%